Sequence specific integration by the family 1 casposase from Candidatus Nitrosopumilus koreensis AR1. Issue 17 (24th August 2021) - Wang, Xiaoke; Yuan, Qinling; Zhang, Wenxuan; Ji, Suyu; Lv, Yang; Ren, Kejing; Lu, Meiling; Xiao, Yibei
Abstract: Casposase, a homolog of Cas1 integrase, is encoded by a superfamily of mobile genetic elements known as casposons. While family 2 casposase has been well documented in both function and structure, little is known about the other three casposase families. Here, we studied the family 1 casposase lacking the helix-turn-helix (HTH) domain from Candidatus Nitrosopumilus koreensis AR1 (Ca. N. koreensis ). The determinants for integration by Ca. N. koreensis casposase were extensively investigated, and it was found that a 13-bp target site duplication (TSD) sequence, a minimal 3-bp leader and three different nucleotides of the TSD sequences are indispensable for target specific integration. Significantly, the casposase can site-specifically integrate a broad range of terminal inverted repeat (TIR)-derived oligonucleotides ranging from 7-nt to ∼4000-bp, and various oligonucleotides lacking the 5′-TTCTA-3′ motif at the 3′ end of TIR sequence can be integrated efficiently. Furthermore, similar to some Cas1 homologs, the casposase utilizes a 5′-ATAA-3′ motif in the TSD as a molecular ruler to dictate nucleophilic attack at 9-bp downstream of the end of the ruler during the spacer-side integration. By characterizing the family 1 Ca. N. koreensis casposase, we have extended our understanding on mechanistic similarities and evolutionary connections between casposons and the adaptation elements of CRISPR-Cas immunity.